The Longriqu fault zone, eastern Tibetan Plateau: Segmentation and Holocene behavior. Issue 3 (8th March 2016) - Ansberque, Claire; Bellier, Olivier; Godard, Vincent; Lasserre, Cécile; Wang, Mingming; Braucher, Régis; Talon, Brigitte; de Sigoyer, Julia; Xu, Xiwei; Bourlès, Didier L.
Abstract: The dextral Longriba fault system (LFS), 300 km long and constituting of two fault zones, has recently been recognized as an important structure of the eastern Tibetan plateau (Sichuan province), as it accommodates a significant amount of the deformation induced by the ongoing Indo‐Asian collision. Although previous paleoseismological investigations highlighted its high seismogenic potential, no systematic quantification of the dextral displacements along the fault system has been undertaken so far. As such information is essential to appraise fault behavior, we propose here a first detailed analysis of the segmentation of the Longriqu fault, the northern fault zone of the LFS, and an offset inventory of morphological features along the fault, using high‐resolution Pleiades satellite images. We identify six major segments forming a mature fault zone. Offsets inventory suggests a characteristic coseismic displacement of 4 m. Two alluvial fans, with minimum ages of 6.7 and 13.2 ka, respectively displaced by 23 ± 7 m and 40 ± 5 m, give an estimate of the maximal horizontal slip rate on the Longriqu fault of 3.2 ± 1.1 mm yr −1 . As a result, a minimum 1340 year time interval between earthquakes is expected. Key Points: The 80 km long section of the Longriqu fault could rupture as a whole during earthquake The inventory of offsets along fault shows evidence for nine past earthquakes The Longriqu fault zone follows a characteristic slip model with a 4 m coseismic slip